Rola funduszy europejskich we wspieraniu rozwoju konkurencyjności i innowacyjności MŚP w Polsce - Wyrwa, Dariusz (Role of European Funds in the Support of Development of Competitiveness and Innovation of Small and Medium Enterprises in Poland, 2006)
Small-medium firms represent more than 99% of Polish firms. They are often too small to make the necessary investments in research and development, but cannot for these reasons reject innovation. This paper stems from the need to know more about how the innovativeness of smaller firms is related to contextual factors. Special attention was paid to importance of innovations for business development, attitude of entrepreneurs to innovations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 679-686